Firefighters’ Exposures to Combustion-derived Polycyclic Aromatic Hydrocarbons and Other Mutagens - Keir, Jennifer Leslie Ann (Université d'Ottawa / University of Ottawa, 2023)
The objective of this thesis was to investigate firefighters’ exposures to carcinogens and mutagens. This thesis aimed to (1) characterize firefighters’ exposures during emergency fire suppression, (2) examine the use of silicone wristbands as passive samplers to assess firefighters’ exposures, and (3) assess the ability of post-fire decontamination protocols to reduce firefighters’ exposures. Chapter 1 provides a general introduction and background information on the concepts covered in this thesis. In Chapter 2, I examined air and surface contamination with polycyclic aromatic hydrocarbons (PAHs) and metals, both at fire stations and following emergency fire suppression activities. I also investigated the ability of current laundering methods to remove surficial PAHs and metals from firefighters’ personal protective equipment. In Chapter 3, I assessed the ability of silicone wristband passive samplers to measure firefighters’ exposures to PAHs during live fire training. In Chapter 4, I assessed the ability of three post-fire dermal decontamination methods to remove surface contamination and reduce internal dose. In Chapter 5, conclusions and implications for each chapter are summarized. Future directions for the field are described. The overall conclusions for this thesis were: i. firefighters experience significant occupational exposures to carcinogens during emergency fire suppression and live fire training; ii. the ability of silicone wristbands to properly sample PAHs is altered in a fire environment and correction factors must be determined to improve their utility for exposure assessment; iii. current post-fire dermal decontamination methods, which are intended to reduce firefighters’ exposures, do not reduce their internal dose of PAHs.
Keywords: Polycyclic aromatic hydrocarbons; Mutagens; Firefighters; Occupational exposures